Temporo-spatial expression of bFGF and TGFβ2 in embryonic dopaminergic grafts in a rat model of Parkinson's disease - Sommer, Clemens; Sabel, Michael; Oertel, Wolfgang H.; Kiessling, Marika; Sautter, Jürgen (Brain research. Molecular brain research, 1999)
In the present study we analyzed the temporo-spatial expression pattern of basic fibroblast growth factor (bFGF) and transforming growth factor beta 2 (TGFβ2) in embryonic dopaminergic transplants in the 6-hydroxydopamine rat model of Parkinson's disease. The grafts differentiated for 1, 2, 4 and 8 weeks, respectively and were then analyzed using antibodies directed against tyrosine hydroxylase, bFGF and TGFβ2. At all time points investigated, grafts contained tyrosine hydroxylase immunoreactive neurons. One week after transplantation the grafts displayed no immunoreactivity for bFGF and TGFβ2. In more mature grafts (starting at 2 weeks post transplantation) bFGF and TGFβ2 immunoreactivity became detectable within the graft and at the graft-host interface but was restricted only to astrocytes. In the striatum surrounding the graft, a transient increase of TGFβ2 immunoreactive astrocytic processes was observed between 1 and 2 weeks after transplantation. This temporo-spatial expression pattern of TGFβ2 immunoreactive astrocytes suggests that the upregulation of TGFβ2 is more likely due to the trauma imposed by the transplantation procedure than to an intrinsic differentiation program. Lack of both bFGF and TGFβ2 expression in grafted dopaminergic neurons compared to their normal expression in the adult rat substantia nigra indicates that these transplanted neurons do not develop their complete physiological phenotype. Together with the observed deficiency in astrocytic bFGF early after grafting this may be responsible for the poor survival of grafted embryonic dopaminergic cells.